Законско и институционално регулирање на пазарот на капитал во Република Македонија и негово усогласување со регулативниот систем на Европската унија - Божиноска, Сања (Економски факултет, УКИМ, Скопје, 2014)
The subject of study in this work present legal and institutional regulation of the capital market in Republic of Macedonia and its adaptation with the regulatory system of the European Union. The capital market is the basic factor for developement of each economy. The development of the capital market is conect with the increasing international competition of the economy and the high standard of living of population. The existence trust in the capital market is one of the fundamentals conditions for inflow and acumulation of capital in the country across attracting the investment. Therefore, for especially role is investigation of the legal and institucional regulation of capital market in the Republic of Macedonia, with distinctive review on the adaptation with the regulatory system of the European Union. After entirely investigation of the legal and institutional regulation of the capital market, it is necessary to seeits adaptation according the European Union and the requirements of the addititonal activities that should take the Republic of Macedonia for whole adaptation according the regulatory system of the European Union. As particular section will be presentation the following the practise of others country in tranzition, now members of the European Union in the section of legalzation and institutions of the capital markets.
Legal and institutional regulation of the capital market in Republic of Macedonia and its adaptation with the regulatory system of the European Union
Keywords: capital market, legal regulation, institutional regulation, adaptation of the capital market, regulatory system, European Union